GETTING BETTER: ALN AND STUDENT SUCCESS - Moore, Janet C.; Sener, John; Fetzner, Marie (Online Learning, 2006)
In the U.S., only 38 of every 100 ninth graders enroll in college; of these 38, only 18 complete bachelors’ degrees within six years. Asynchronous learning networks (ALN)—asynchronous, highly interactive, instructor-led, resource-rich, cohort-based learning—can yield high success rates. Growing demand for online education and the expectation among higher education leaders that ALN learning outcomes will exceed face to face outcomes reflect belief in ALN’s power to engage learners. Sloan-C’s body of research confirms that ALN is especially suited for the anytime, anywhere, affordable access that is responsive to learners in a knowledge society. In fact, the original principles of ALN are the same principles that characterize ALN programs that have high student success rates. This paper includes vignettes from two- and four-year ALN programs that have used these principles to achieve high success rates.